ASSOCIATION BETWEEN NUTRITIONAL STATUS AND SLEEP QUALITY AMONG PATIENTS WITH CANCER: Nutritional status and sleep quality among cancer patients - Vanoh, Divya; Hii, Seng Wei (Malaysian Journal of Public Health Medicine, 2021)
Cancer is associated with high malnutrition risk and poor sleep quality which affects the quality of life of the patients. Thus the aims of the study is to determine the association between nutritional status and sleep quality among cancer patients in Malaysia. This is a cross sectional study conducted among 75 cancer patients in both the out and inpatient settings in Hospital Universiti Sains Malaysia (HUSM) from January to March 2020. Socio-demographic characteristics, medical history, anthropometry data, nutritional status assessment by Body Mass Index (BMI) and Patient-Generated Subjective Global Assessment (PG-SGA) and sleep quality assessment by Pittsburgh Sleep Quality Index (PSQI) were obtained. Among the 75 subjects, 39 subjects (52.0%) were women and 36 subjects (48.0%) were men. According to PG-SGA, 45 subjects (60.0%) were malnourished. According to PSQI, 48 subjects (64.0%) claimed of poor sleep quality. Nutritional status assessed using BMI was not significantly associated with sleep quality (P = 0.289) while nutritional status assessed using PG-SGA was significantly associated with sleep quality (P ? 0.001). Those with good sleep quality were mostly in the category of well-nourished based on PG-SGA scoring. Regression analysis revealed that declining nutritional status was related to poor sleep quality (p<0.05). There is a significant association between nutritional status and sleep quality among cancer patients and this is essential to be investigated to improve quality of life of cancer patients.